2017
DOI: 10.1155/2017/9830342
|View full text |Cite
|
Sign up to set email alerts
|

Antiemetic and Myeloprotective Effects of Rhus verniciflua Stoke in a Cisplatin‐Induced Rat Model

Abstract: Rhus verniciflua Stoke has been commonly used in traditional medicine to treat gastrointestinal (GI) dysfunction diseases. In order to investigate pharmacological properties of Rhus verniciflua Stoke water extract (RVX) on cisplatin-induced amnesia, RVX (0, 25, 50, or 100 mg/kg) was orally administrated for five consecutive days after a single intraperitoneal injection of cisplatin (6 mg/kg) to SD rat. Cisplatin injection significantly increased the kaolin intake (emesis) but reduced the normal diet intake (an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 37 publications
3
16
1
Order By: Relevance
“…The histological studies of BM during chemotherapy are poorly reported in the literature. However, similar results were only observed with preventive treatment with L. casei CRL431 (15), or with natural compounds derived from herbal plants, like Ginseng or Rhus verniciflua using different models of immunocompromised hosts (34,35). Moreover, our histological results were correlated with the cell total counts and cell morphologically recognizable counts in both BM and blood.…”
Section: Discussionsupporting
confidence: 81%
“…The histological studies of BM during chemotherapy are poorly reported in the literature. However, similar results were only observed with preventive treatment with L. casei CRL431 (15), or with natural compounds derived from herbal plants, like Ginseng or Rhus verniciflua using different models of immunocompromised hosts (34,35). Moreover, our histological results were correlated with the cell total counts and cell morphologically recognizable counts in both BM and blood.…”
Section: Discussionsupporting
confidence: 81%
“…Several studies have demonstrated the myeloprotective effect of some plant extracts or their active metabolites in chemotherapy. For example, the aqueous extract of R. verniciflua (also from the Anacardiaceae family, such as A. adstringens ) improves the resistance of rats to the adverse effects of chemotherapy in the gastrointestinal tract and the bone marrow [ 5 ]. Similarly, curcumin, a natural polyphenol, increases the tolerance of bone marrow cells to the toxic effects produced by chemotherapy and suppresses the defective hematopoiesis induced by tumor-derived VEGF in a tumor model [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, curcumin, a natural polyphenol extracted from turmeric, attenuates CbPt-induced myelosuppression and increases the survival rate of tumor-bearing animals [ 4 ]. Similarly, treatment of rats with extracts from the lacquer tree ( Rhus verniciflua Stoke) improves the resistance of rats to cisplatin chemotherapy-related adverse effects in the gastrointestinal tract and bone marrow [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 5‐HT acting on epithelial 5‐HT 3 receptor is involved in cisplatin‐induced anorexia and gastric dysmotility . Hence, cisplatin induces the release of 5‐HT from the small intestine (EC cells) and stimulates 5‐HT 3 receptors on gastrointestinal vagal afferents to initiate the vomiting reflex, gastric distension, and delayed gastric emptying . As shown in Figure A, although the serotonin released from intestinal in our experiments was not measured, cisplatin was able to elevate intestinal TPH‐1 activity, which suggesting the production of serotonin may be increased from intestinal EC cells and contributing to gastrointestinal disorders.…”
Section: Discussionmentioning
confidence: 63%